ナンキョク オオガタ セツジョウシャ (SM100S) ノ カイハツ I. ヒツヨウセイ ト カイハツ ケイイ - 竹内, 貞男; タケウチ, サダオ; 喜納, 淳; キノウ, アツシ; 細谷, 昌之; ホソヤ, マサユキ; 吉田, 治郎; ヨシダ, ジロウ; 石沢, 賢二; イシザワ, ケンジ; Takeuchi, Sadao; Kino, Atsushi; et al. (1992)
P(論文) 日本南極地域観測隊は, これまで4種類の雪上車を使って調査活動を続けてきた。それらの雪上車は用途別に内陸氷床上用と沿岸・海氷上調査用の2つに分類できる。内陸用の雪上車はこれまでSM50S型中型雪上車を使用してきたが, 「南極氷床ドーム深層掘削計画」も提言されるなど, 調査区域が年々内陸奥地に広がり, より低温性能のよい大型雪上車の開発が要望されていた。そのため, 国立極地研究所設営専門委員会に雪上車設計作業委員会を設置して, 現有のSM50Sの技術的課題を分析し, この結果を基に新型雪上車の開発を実施した。この雪上車は国内での試験走行の後, 1991年に南極に搬入され, 1992年の冬期には南極氷床で走行し, ほぼ予想された性能を発揮した。 Four types of snow vehicles have so far been employed in the Japanese Antarctic Research Expedition. These snow vehicles are mainly used on the inland ice sheet and on the sea ice. As for the inland traverses, the SM50S-type snow vehicle has been used, but the research area is now expanding to the much colder area, and the "Deep Ice Coring Project at Dome Fuji, East Antarctica" has recently been proposed. Therefore, a committee for the design of a new snow vehicle was organized in the special committee on logistics of National Institute of Polar Research. The committee made the design of a new snow vehicle capable of operating under very cold and low pressure conditions. The newly developed snow vehicle was operated on the Antarctic ice sheet in the winter of 1992,and the performance was almost just as expected. departmental bulletin paper